2009
DOI: 10.1016/j.joca.2008.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Autologous conditioned serum (Orthokine) is an effective treatment for knee osteoarthritis

Abstract: The data demonstrate that ACS injection considerably improves clinical signs and symptoms of OA. It remains to be determined whether ACS is disease-modifying, chondroprotective, or chondroregenerative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
249
1
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(274 citation statements)
references
References 58 publications
(28 reference statements)
12
249
1
12
Order By: Relevance
“…Previously, Baltzer et al 11 reported the effectiveness of Orthokine to treat mild to moderate knee pain. One of the clinical outcome benchmarks assessed by the authors was also a >50% reduction in VAS pain scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Baltzer et al 11 reported the effectiveness of Orthokine to treat mild to moderate knee pain. One of the clinical outcome benchmarks assessed by the authors was also a >50% reduction in VAS pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…22 Our novel autologous conditioning processing, Arthrokinex TM (ACS), and subsequent standardized protocol, was developed following the success of treatment strategies such as Orthokine and Arthrex that induced IL-1-Ra from whole blood. 10,11 Arthrokinex TM (ACS) offers an interventional orthopedic treatment plan at the molecular level and it incorporates the inhibition of IL-1b through the rapid induction of IL-1-Ra. We have previously demonstrated that our novel formulation produces IL-1-Ra levels that are consistently adequate to block the IA destructive effects of IL-b.…”
Section: -14mentioning
confidence: 99%
“…Recently, the effect of autologous conditioned serum (with glass-chromium beads) was evaluated in an experimental model of equine OA (Wehling et al 2007). It has been observed that equine or human serum conditioned with chromium stimulates supraphysiological production of IL-1ra and other GFs and cytokines (IL-10, IL-1, TNF-α, IGF-1, and TGF-β 1 , amongst others) (Baltzer et al 2009, Hraha et al 2011.…”
Section: Autologous Conditioned Serum (Acs)mentioning
confidence: 99%
“…Bei einer aktuellen humanmedizinischen Studie an 376 Probanden, von denen 134 eine Behandlung der OA des Kniegelenks mit ACS, 135 mit HA und 107 mit NaCl erhielten, zeigten die Patienten nach ACS-Injektion eine deutliche Besserung der klinischen Symptome und eine gesteigerte Lebensqualität (Baltzer et al 2009). Die Therapie unter der Verwendung von Eigenblut verspricht eine gute Verträglichkeit und die beschriebenen Studien sind viel versprechend.…”
Section: Die Inkubation Von Eigenblut Mit Borosilikatglasperlen Derenunclassified